2018
DOI: 10.1039/c8cc00086g
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic charge acceptance and hydrogen evolution of a new MXene additive in advanced lead-acid batteriesviaa rapid screening three-electrode method

Abstract: A methodology to screen additives in lead-acid batteries is critical. We developed a three-electrode system that can rapidly check the dynamic charge acceptance (DCA) and hydrogen evolution of electrodes. The electrode with 2% MXene and 0.2% carbon black shows a better DCA, which indicates its great potential in the start-stop technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Two-dimensional (2D) materials occupy a low surface density due to the large surface area. Compared to their bulk form, 2D materials have other alluring characteristics including high electrical conductivity and glorious mechanical properties, which are beneficial for electrocatalysts. MXenes are a family of 2D transition metal carbides which have been intensively studied in recent years and are expanding rapidly in both types and applications. They are also studied as efficient electrocatalysts for water splitting, ORR, nitrogen reduction reaction, and alcohol oxidation reactions. Of all MXenes, Ti 3 C 2 T x gets the most attention. Researchers have found that, compared to commercial carbon supports, the interactions between the Pt nanoparticles and the MXene (Ti 3 C 2 T x ) substrate can prevent the agglomeration of Pt nanoparticles during electrochemical reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials occupy a low surface density due to the large surface area. Compared to their bulk form, 2D materials have other alluring characteristics including high electrical conductivity and glorious mechanical properties, which are beneficial for electrocatalysts. MXenes are a family of 2D transition metal carbides which have been intensively studied in recent years and are expanding rapidly in both types and applications. They are also studied as efficient electrocatalysts for water splitting, ORR, nitrogen reduction reaction, and alcohol oxidation reactions. Of all MXenes, Ti 3 C 2 T x gets the most attention. Researchers have found that, compared to commercial carbon supports, the interactions between the Pt nanoparticles and the MXene (Ti 3 C 2 T x ) substrate can prevent the agglomeration of Pt nanoparticles during electrochemical reactions .…”
Section: Introductionmentioning
confidence: 99%